CORRELATION CONNECTIONS OF CALCIUM METABOLISM DISORDERS IN CHILDREN WITH PAROXYSMAL AUTONOMIC FAILURE AGAINST THE BACK PATHOLOGY OF THE CERVICAL SPINE - Maidannyk, V.; Mityuryayeva, I.; Hnyloskurenko, H.; Kreposniak, A.; Dotson, S.; Churilina, A.; Kornienko, A. (Проблеми клінічної педіатрії, 2019)
Introduction. Paroxysmal autonomic failure is one of the pathogenetic forms of autonomic dysfunction. As a result of overloading the autonomic nervous system and disruption of adaptation processes, vegetative crises arise in the body, which are called paroxysms. In recent years, the number of patients has increased and accounts for almost half of all children with clinical forms of autonomic dysfunction [6]. The purpose of this study is to study the correlation of the elemental composition of nutritional status, blood serum, hair, bone mineral density, physical development of children who suffer from paroxysmal vegetative insufficiency against the background of different X-ray manifestations of the cervical spine pathology. Materials and methods of research. We examined 204 children aged 8-17 years with paroxysmal autonomic failure who underwent a clinical and instrumental examination on the basis of the Center for Vegetative Dysfunctions of Children’s Clinical Hospital No. 6 in Kyiv. Instrumental examination included radiography of the cervical spine with functional tests, X-rays of the 1st and 2nd cervical vertebrae through the open mouth, electrocardiography, ultrasound examination of the abdominal cavity organs, rheoencephalography, electroencephalography, daily monitoring of blood pressure, consultations of the neurologist and orthopedistvertebrologist. Results. A Correlation analysis was compiled of the nutrient content in the daily volume of food, elemental composition of the blood and the radical hair zone, with indices of the pathology of roentgenography of the cervical spine and bone mineral density, with an estimate of the body mass index in children aged 8-17 years. Patients with paroxysmal vegetative insufficiency were measured against the background of various manifestations of the cervical spine pathology. Conclusions. The correlation between the indicators of osteopenia and osteoporosis according to the densitometry with copper deficiency (r=0.304, p<0.05), which through the bromine level (r=0.379, p<0.05) affects the calcium deficiency in blood serum (r=0.359, p<0.05). It is important that the decrease in bone mineral density is associated with changes in physical development, more often in the side of body weight increase with r=0.322, p<0.05, which proves the provoking importance of these microelements in the development of metabolic changes in patients.It was found that the deviation from the normative body mass index in patients with paroxysmal vegetative insufficiency in the presence of the cervical spine pathology is associated with a deficiency of manganese and zinc, which requires the use of appropriate medications in complex treatment drugs to improve the effectiveness of therapy.